Predictors of Sleep Duration and Sleep Disturbance in Children of a Culturally Diverse Region in North-Eastern Greece - Evangelia Nena (Frontiers in Pediatrics, 2020)
Background Aim: The aim of this study was to examine the sleep characteristics of children and explore associations with various socio-demographic factors in an area of Greece characterized by cultural diversity.Methods: A questionnaire about children's sleep habits had been distributed to parents of children who visited the pediatric outpatient clinic of University General Hospital of Alexandroupolis for a medical examination and to get a health certificate for participation in sports activities. Children with chronic health conditions were excluded.Results: In the study, 449 children (27.1% belonging to minorities) were included, aged 7.6 ± 2.9 years. Most of them (81.7%) slept after 10 p.m., with a mean nocturnal sleep duration of 9.4 ± 1.2 h. The most commonly reported disturbance was snoring (26.2%). Age and high educational level of the mother were both important determinants for sleeping late [OR 1.139 (1.033–1.255); p = 0.009 and OR 1.086 (1.004–1.175); p = 0.040, respectively]. The latter was also associated with an absence of any reported sleep disorder in children [OR 0.934 (0.877–0.994); p = 0.031]. A longer sleep duration was reported among Roma children (p = 0.022), which was more overt in girls (mean sleep duration 10.4 ± 1.6 h). In the Roma group also, the prevalence of sleep disorders was higher.Conclusion: Age progression and maternal educational level, along with cultural background, seem to be correlated with variations in the sleep characteristics of children in a culturally diverse population in Greece.